The Impact of Geriatric Assessment on Patient Outcomes in Radiation Oncology: A Pilot Study. - Leech, Michelle; O'Donovan, Anita (My University, 2020)
Introduction: The objective of this pilot study was to obtain preliminary data on the efficacy and feasibility of incorporating geriatric assessment (GA) into radiation oncology (RO) with regard to patient outcomes and treatment decisions. Materials and Methods: Feasibility was assessed via the percentage of patients able to complete certain aspects of the assessment on their own, or with the assistance of a carer before appointments, was recorded. Consultation times and referrals were also documented. All participants (n=30) underwent GA at baseline, before randomisation to the intervention/control arm and commencement of radiotherapy treatment planning procedures. The results of GA were relayed to the Radiation Oncologist (RO) for the intervention arm only. GA was repeated for each participant three months after the completion of radiotherapy. Results: There was some evidence of increasing dependence, at three month follow-up, in ADLs and IADLs, less mobility (TUG score), higher GDS scores and increased vulnerability. However, these were not statistically significant. All patients underwent their predefined radiotherapy treatment plan, without modification. A number of deficits on GA were identified that may be considered significant for older patients. Conclusion: The impact on decision making may reflect a lack of experience and familiarity with GA and how to interpret it, as well as an obvious gap in the literature as to how it affects radiotherapy patient outcomes.
PUBLISHED
Keywords: Pilot study, radiotherapy, aging, cancer, geriatric assessment, treatment decisions; Cancer; Radiation Therapy